Study of dry etched N-polar (Al)GaN surfaces obtained by inductively coupled plasma etching - Ge, Xiaoming; Yin, Xuebing; Zeng, Qiaoyu; Feng, Qi; Wang, Xiaohui; Li, Quantong; Chen, Zhitao; Li, Chengguo (Frontiers in Physics, 2022)
We report the Cl-based inductively coupled plasma etching of N-polar Al(Ga)N layers obtained from layer transfer. It is found that debris appeared on the etched N-polar surface after exposing in air for a short period whereas the etched Al-/Ga-polar surface was clean and smooth. The debris can be completely self-vanished on the N-polar Al0.4Ga0.6N surface after exposing in air for a few hours but still remained on the N-polar GaN surface even after over one month. The surface chemical analysis results suggested that the debris is the result of Cl-related byproduct generated during the etching process. Byproducts like Al(Ga)Clx and its derivatives are believed to cover on the N-polar surface after the ICP etching and increase the etched surface roughness significantly. The formation and disappearance of debris are attributed to the formation of Al(Ga)Clx⋅ 6H2O crystals when Al(Ga)Clx absorbs moisture in the air and its spontaneous decomposition on the N-polar surface, respectively. Adding O2/SF6 in the process helps remove Al(Ga)Clx byproducts but at the cost of roughened surface/reduced etch rate. With an additional cleaning process after etching, an uniform and smooth N-polar GaN surface with a low root-mean-square surface roughness of 0.5 0.6 nm has been successfully obtained at a reasonable etch rate ( 150 nm/min). The results can provide valuable guidance for the fabrication of high-performance N-polar GaN devices.